A Synchrotron X-Ray Study of Texture Induced by Application of Magnetic Fields During Phase-Transformations in Shape-Memory Ni-Mn-Ga - Vaidyanathan, R.; Yilmaz, S.; O'Handley, R.C.; Dunand, D.C. (Springer Science and Business Media LLC, 2001)
AbstractNi-Mn-Ga alloys can exhibit a thermoelastic phase transformation near room temperature, which is associated with the shape-memory effect (i.e., temperature-induced strain recovery after twinning) or superelasticity (i.e., strain recovery after a stress-induced phase transformation). This work uses a synchrotron X-ray transmission technique to investigate texture induced by applying magnetic fields during the phase transformation in polycrystalline Ni2MnGa. Synchrotron X-ray radiation is ideally suited for such investigations since the measurements are representative of twinning in the bulk, in contrast with measurements from conventional X-ray sources that represent surface measurements affected by surface relaxation. Magnetic texturing of polycrystalline Ni2MnGa, by cooling through the phase-transformation in the presence of a magnetic field, has potential to lead to polycrystalline materials with more compatible field- induced strains and hence increased twin boundary mobility upon application of a magnetic and/or stress field.